Psychometric Intelligence and Academic Achievement, A Comparative Analysis of Elementary Schools - Sunita Malhotra (STAI Miftahul Ula Nganjuk, 2020)
Intelligence and achievement are two different, but interrelated, constructs (Kaya, Juntune, & Stough, 2015). They have been studied for over a century in an attempt to explain differences in educational and life outcomes. School achievement may be considered a resultant of the total growth pattern of the child. Growth in interest and in attitudes towards learning is as important as growth in knowledge. Learning methods of solving problems is fully as valuable as the facts gained or improvements made in school or community in the process. The present research focuses on the primary school children’s academic achievement and Intelligence level. The sample for the present study consisted of 150 students from different types of schools such as of NGO’s based school, Government school and Private primary schools of the different regions of India. The Raven’s Colored Progressive Matrices was used for measuring the IQ level of the students and for measuring the Academic Achievement, Achievement Test Battery of Singh (ATB-SR), 2008 which consists of test Hindi, English, Mathematics, Science and Social Science. The results revealed that there was a significant difference between the achievement scores of Hindi, English, Mathematics, Science and Social Science of the NGO’s based school, government and private school students. Important implications for educational practices may derive from these findings since they can provide valuable information to design instructional actions and programs that can improve student achievement and satisfaction.